Analisis Kemampuan Membaca Arab Melayu Mahasiswa Kelas 2021 B Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Riau - Tiara Andinie Parmitha Sisiliaudra; Serly Kusnawi; Tifani Indah Prasiti; Hasnah Faizah AR (Universitas Maritim AMNI Semarang, 2024)
The ability to read Malay Arabic in higher education needs to be taken into account because it is based on high level education, therefore this research aims to determine the ability to read Malay Arabic writing for students in class 2021B, Indonesian Language and Literature Education Study Program, FKIP, University of Riau, academic year 2023. To determine the ability In reading Malay Arabic writing, the author uses several methods, namely by testing the skills of reading Malay Arabic writing. The research method uses descriptive analysis, the research sample was taken from 35 students in class 2021B, semester 5 of Indonesian Language and Literature Education, FKIP, Riau University in 2023. The data collection technique was carried out by conducting a reading skills test for 2021B students. The data analysis technique is carried out by processing the data that has been obtained using a reading trial test. The data analysis technique is by collecting test results, looking for percentages for each aspect of reading speed and comprehension. The results of the research concluded that the Malay Arabic reading skills of students in the 2021B Indonesian Language and Literature Education Study Program FKIP Riau University were 26 students in the high category, 7 students in the medium category and 2 students in the low category.